Why blockchain needs graph: A survey on studies, scenarios, and solutions - Song, Jie; Zhang, Pengyi; Qu, Qiang; Bai, Yongjie; Gu, Yu; Yu, Ge (Journal of parallel and distributed computing, 2023)
The popularity of blockchain platforms and their applications in industry and academia keeps rising. The multifarious requirements stimulate another technique, graph data and algorithms, to join the blockchains; thus, studies, scenarios, and solutions about graph-related blockchains have emerged. This paper aims to see whether the state-of-the-art studies satisfy the applications through a comprehensive survey on graph-related blockchains. To answer why a blockchain needs graphs in general, we analyze literature about blockchain and graph, as well as use cases on the application-oriented and graph-related scenarios collected from practical blockchain projects. The paper summarizes three graph-related blockchain studies: graph algorithms for blockchains, graph data in blockchains, and graph applications on blockchains. Based on these summarization, it figures out the gaps between the studies and the applications, that is, few of studies natively integrate graph computing into a blockchain. Here, the “graph integration” means processing on-chain graph data, which contains blockchain information, in a real-time, distributed, and consensual manner. We propose the prospect of the Graph-integrated Blockchain Platform (GiBP for short), and explain why a GiBP is inevitable, the challenges of a GiBP, and the GiBPs' main functions and features people expect for future research. •Summarize and classify prior works on existing graph-related blockchains.•Summarize and refine prior works on graph-related blockchains.•Draw the gaps between the studies and the applications of graph-related blockchain.•Propose the prospect of the Graph-integrated Blockchain Platform (GiBP for short).